(untitled) (Applied Biological Research, 2020)
An experiment was conducted to assess the effect of replacement of maize by animal-fat on the growth and feed conversion efficiency in Large White Yorkshire pigs. Thirty weaned piglets were randomly divided into three groups and allotted to the three dietary treatments [control ration (as per NRC, 1998), 50% maize of control ration replaced by animal-fat and 100% maize of control ration replaced by animal-fat] and maintained for 70 days. The daily feed intake and fortnightly body weight were recorded and average daily gain and feed conversion efficiency calculated. The average daily gain and feed conversion efficiency were found to be 813.0, 769.8, 678.4 g and 2.80, 2.88, 3.08, respectively, for the three respective treatment groups. There was no significant difference in the performance of pigs belonging to control ration group and the group fed with 50% maize of control ration replaced by animal-fat, but 50% replacement had higher average daily gain and feed conversion efficiency than the group fed with 100% maize of control ration replaced by animal-fat. The study revealed that the pigs fed diet having 50% maize replaced by animal-fat performed in a similar way to that of control fed group and was better than those pigs fed diet with 100% replacement of maize by animal-fat.